Approximation of Macedonian agriculture and rural development to European Common agricultural policy - Gjosheva Kovachevikj, Marija (Faculty of Economics, University in Nis, 2013)
During the pre-accession process, Macedonia as a candidate country strives to harmonize its legislation with the EU acquis communautaire, adapt its institutions and economic policies, strengthen the rule of low and develop market oriented economies. The objective of the paper is to describe Common Agriculture Policy and to identify performance of the Macedonian agriculture as one of the most important sectors in the national economy and the most complex in the EU accession negotiation process. Despite challenges and difficulties during the adaptation period, the adjustment of Macedonian agricultural development level to EU standards implies variation of agricultural economic performance, generally accompanied by polarization between the successful, organized, market oriented farmers and farmers on small non-competitive farms. Before real EU accession negotiation start, it is crucial for policy makers and the general public in Macedonia to consider what can be done to get the most out of the good ones.
Keywords: CAP, agriculture, rural development, pre-accession